Comparison of muscle cross-sectional areas between weight lifters and wrestlers - Kanehisa, H.; Ikegawa, S.; Fukunaga, T. (International Journal of Sports Medicine, 1998)
The purpose of this study was to investigate the difference in the magnitude of muscular development between Olympic weight lifters and wrestlers through the measurements of fat-free mass (FFM) and limb muscle cross-sectional area (CSA). Subjects were college Olympic weight lifters (N = 34, age = 20.0 +/- 1.3 years, stature = 1.67 +/- 0.07 m, body mass = 70.1 +/- 10.2 kg, X +/- SD) and wrestlers (N = 33,20.3 +/- 1.2 years, 1.69 +/- 0.06 m, 71.0 +/- 1.8 kg) who had identical range of body mass. Body density and the CSAs of reciprocal muscle groups in the forearm, upper arm, lower leg and thigh were measured by underwater weighing and B-mode ultrasound methods, respectively. No significant difference was found in body density between the weight lifters (1.077 +/- 0.007 g x ml(-3)) and wrestlers (1.076 +/- 0.008 g x ml(-3)). Moreover, FFM and the CSA values of all muscle groups tested were similar in the two groups of weight-classified athletes, with an exception that the wrist flexor CSA was significantly larger in wrestlers than in weight lifters, and the knee extensor and thigh (extensors + flexors) CSAs were larger in weight lifters than in wrestlers. The total muscle CSA of every site was significantly correlated to FFM2/3 in the separate groups; r = 0.714 to 0.815 (p < 0.05) in weight lifters and r = 0.769 to 0.919 (p < 0.05) in wrestlers. While the CSA-to-FFM2/3 ratios of the upper arm and wrist flexor muscles were significantly higher in wrestlers than in weight lifters, those of the thigh and knee extensor muscles were higher in weight lifters than in wrestlers. Thus, the present results suggest that an event-related difference exists in the magnitude of limb muscle CSA between competitive weight lifters and wrestlers of similar FFM.